2010
DOI: 10.1128/aem.02118-09
|View full text |Cite
|
Sign up to set email alerts
|

Spinacia oleracea L. Leaf Stomata Harboring Cryptosporidium parvum Oocysts: a Potential Threat to Food Safety

Abstract: Cryptosporidium parvum is a cosmopolitan microscopic protozoan parasite that causes severe diarrheal disease (cryptosporidiosis) in mammals, including humans and livestock. There is growing evidence of Cryptosporidium persistence in fresh produce that may result in food-borne infection, including sporadic cases as well as outbreaks. However, drinking and recreational waters are still considered the major sources of Cryptosporidium infection in humans, which has resulted in prioritization of studies of parasite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(32 citation statements)
references
References 30 publications
(37 reference statements)
0
32
0
Order By: Relevance
“…Cryptosporidium's resistance to chlorine has also been reported in other studies (8,15). Furthermore, because Cryptosporidium oocysts have been shown to be internalized through the stomata and because they resist hours of washing, the risk of not eliminating Cryptosporidium oocysts from contaminated vegetables by chlorinated washing bath is even greater (16,19). These findings have implications for the safety of minimally processed and ready-to-eat vegetables as these products are assumed to be safe and free of pathogens by the consumers who do not further wash the products before consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium's resistance to chlorine has also been reported in other studies (8,15). Furthermore, because Cryptosporidium oocysts have been shown to be internalized through the stomata and because they resist hours of washing, the risk of not eliminating Cryptosporidium oocysts from contaminated vegetables by chlorinated washing bath is even greater (16,19). These findings have implications for the safety of minimally processed and ready-to-eat vegetables as these products are assumed to be safe and free of pathogens by the consumers who do not further wash the products before consumption.…”
Section: Discussionmentioning
confidence: 99%
“…Parasite-particle complexes exhibit a greater specific gravity and cannot be readily separated by flotation (55,90,98), whereas particles can also mask the antigenic sites at the parasite surface, thus hampering the antigen recognition by specific antibodies that are used for IMS or immunofluorescence techniques. The use of dispersant solutions, chelating agents, detergents, or biosurfactants is not always successful in preventing unwanted parasite-particle interactions during sample processing (54,75). Furthermore, the surfaces of purified parasites may be still coated with divalent cations and organic substances (humic and fulvic acids) that may interfere with downstream applications such as PCR, which usually give useful information on the species, viability, and genetic type of the detected parasites (41,58,102).…”
Section: Implications For Natural Resource Managementmentioning
confidence: 99%
“…Alternatively, it may be that microsporidia spores are capable of strong adhesion to or internalization in, certain types of product, thereby successfully evading the effects of washing and disinfection. A research conducted in the USA demonstrated that Cryptosporidium oocysts were capable of strongly adhering to spinach plants after contact with contaminated water and were also internalized within the leaves, thus making washing entirely ineffective [54].…”
Section: Discussionmentioning
confidence: 99%